Qualidade do sono em pacientes com síndrome do túnel do carpo - Pereira, Breno José Hülle [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Frequently the symptoms of the carpal tunnel syndrome (CTS) occur at night time, but the relation between CTS and the sleep characteristics of those patients have yet to be systematically described by objective methods, such as conduction studies (ENMG) and polysomnography (PSG), which is the aim of this study. Methods: Consecutive female patients with CTS diagnosed by ENMG were studied by polysomnographic exams and listed in accordance with CTS severity, evaluated by distal motor latency of the median nerve of the affected hand or hands, and their polysomnographic data were analysed. Results: 42 patients were studied from June 2011 to June 2015. The Arousal Index (AI) of the patients with severe CTS were altered in larger proportion of those individuals than in those patients with slight or moderate CTS (100, 60% and 66%, respectively). This relation was also prevalent when the Desaturation Time (DT) was analyzed. Alterations of the Sleep Efficiency (SE) were more common among patients with bilateral CTS. Sleep architecture was equally altered among all patients, with slow wave sleep (SWS) and REM sleep diminished in all groups. The presence of Obstructive Sleep Apnea (OSA) was not dependent on CTS severity. Conclusions: The larger the CTS severity evaluated by ENMG, the more prevalent were fragmented sleep and sleep desaturation. Further analysis is required to ascertain causal relations between sleep quality and CTS severity.

Frequentemente os sintomas da síndrome do túnel do carpo (STC) ocorrem à noite, mas a relação entre STC e características do sono destes pacientes ainda não foram sistematicamente investigadas através de métodos objetivos, tais como a eletroneuromiografia (ENMG) e a polissonografia (PSNG), o que constitui o objetivo deste estudo. Métodos: Pacientes do sexo feminino com STC, diagnosticadas por estudo de condução nervosa (ENMG), foram estudadas por exames de polissonografia e listadas de acordo com a gravidade da STC, mensurada pela latência motora distal (LMD) do nervo mediano da mão ou mãos afetadas, e seus dados polissonográficos foram analisados. Resultados: 42 pacientes foram estudadas de Junho de 2011 a Junho de 2015. O Índice de Despertares (ID) das pacientes com STC acentuada mostrou-se alterado em uma porcentagem maior do que nas pacientes com STC leve ou moderada (100, 60 e 66%, respectivamente). Essa relação de prevalência se manteve quando o Tempo de Dessaturação (TD) foi analisado. Alterações da Eficiência do Sono (ES) foram mais comuns em pacientes com STC bilateral. Arquitetura do sono está igualmente alterada em todos os pacientes, com sono de ondas lentas (N3) e sono REM diminuídos em todos os grupos. A presença de Síndrome da Apneia Obstrutiva do Sono (SAOS) não dependeu da gravidade da STC. Conclusões: Quanto mais grave a STC documentada por ENMG, mais prevalente é o sono fragmentado e a dessaturação do sono. No entanto, analise aprofundada é necessária para se estabelecer relações entre a qualidade do sono e a gravidade da STC.
Sleep quality in patients with carpal tunnel syndrome
Keywords: Sleep; Polysomnography; Carpal tunnel; Conduction studies; Sono; Polissonografia; Túnel do carpo; Eletroneuromiografia